Physicochemical and antioxidant properties of Coffea arabica honey from Western Oromia, Ethiopia - Admassu Addi; Tura Bareke; Deresa Kebebe; Tolera Kumsa; Kasim Roba (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Coffea arabica is one of the most widely consumed and marketed commodities in the world. The study was designed to characterize C.arabica honey for botanical composition, physicochemical parameters, and antioxidant properties of honey. Twelve honey samples of C. arabica honey were collected during the flowering period of coffee flowers from the Zander hive. The physicochemical properties of honey and the Botanical origin of honey were determined based on Harmonized methods of the International Honey Commission. The antioxidant power of the coffee monofloral honey samples was determined by dissolving 1.5 gm of honey with 25 ml distilled water and mixing it with 25ml methanol and placed at 25◦C for sixty minutes of maceration using a temperature shaker. The pollen count percentage from honey indicated that all honey samples collected from Gera, Gomma, Yayu, and Manna districts were identified as coffee monofloral honey representing 84%, 93%, 75%, and 73 % of pollen count respectively. The mean moisture, ash, HMF, EC, FA, pH, fructose, glucose and sucrose content of Coffea arabica honey were 22.48%, 0.21%, 11.88, 0.49 mS/cm, 13.44 meq/Kg, 3.32, 32.77%, 32.9%, and 3.57% respectively. The total phenol and flavonoid content range from 42.1-82.1 and 21.7-59.7 mg/100 g of GAE/g respectively while the radical scavenging activity ranges from 60.2- 66.3%. The pollen analysis of honey from the area is coffee monofloral honey since its pollen count exceeds more than 45% and the honey quality also meets the Ethiopian and International standards. The antioxidant power of Coffee honey has a considerable amount of polyphenolics which have relevant antiradical activity.